Texts, Language, and History in the Madhab-Law Tradition: A Study of the Shāfiʿī School - Ghanem, Tarek (AUC Knowledge Fountain, 2020)
This thesis advances the study of the legal literature from the madhhab-law tradition by way of studying the Shāfiʿī literary tradition and its two most authoritative classics. These two works are al-Nawawī’s (d. 676/1278) digest Minhāj al-ṭālibīn and Ibn Ḥajar al-Haytamī’s (d. 974/1567) commentary on it, Tuḥfat al-minhāj. This study will provide a typology of the development of the Shāfiʿī juristic texts. The typology is based on an indigenous and coherent periodization centered around an analysis of the intellectual and social developments within the Shāfiʿī legal tradition, not the classical Eurocentric periodization scheme. The main objective of this typology is to present a coherent theory of texts that can serve our understanding in two main ways. First, it will help situate these texts within overarching discursive developments in the Shāfiʿī legal tradition. Second, it will contribute to a coherent understanding of how discursive arguments emerged, interacted, and transpired across time and space. More specifically, it will help us understand how and why these works emerged at the time, what social and scholarly functions they served, what role language and nomenclature played in serving these functions, how they acquired their authoritative status, and what overarching conversations they engaged with. The Shāfiʿī madhhab is a discursive tradition that can be understood from multiple perspectives. I analyze the particularities of its intellectual history through a historiographical lens to trace how agreements and disagreements, both internal and external, were managed by jurists and through texts. Starting with the eponymous founder, Muḥammad b. Idrīs al-Shāfiʿī (150-204/767-820), I present a coherent narrative of the interpretive developments of the Shāfiʿī literary tradition as a ‘story of books.’ This narrative will elucidate how and why literary genres, juristic operations, and particular texts emerged, with a special focus on how to situate Minhāj and Tuḥfa in Shāfiʿī literary history. Both al-Nawawī’s digest Minhāj and Ibn Ḥajar’s commentary on it, Tuḥfa, will be analyzed textually. I will analyze each text, its genealogy, the reasons it was authored, its particular linguistic and terminological makeup, juristic objectives and achievements, and examples from its juristic trajectory that demonstrate its different functions. A central interest of this thesis is how each of the texts represent and contribute to the development of the genres of digests (mukhtaṣarāt) and expansums (muṭawwalāt). The authors’ innovations in the realm of juristic terms (al-muṣṭalaḥāt al-fiqhiyya) will be investigated to prove the centrality of these terms to their juristic projects.